EVALUATION OF THE ANTIMICROBIAL PROPERTIES OF DIFFERENT PARTS OF CITRUS AURANTIFOLIA (LIME FRUIT) AS USED LOCALLY - Aibinu, Ibukun; Adenipekun, Tayo; Adelowotan, Toyin; Ogunsanya, Tolu; Odugbemi, Tolu (African Journal of Traditional, Complementary and Alternative Medicines, 2006)
We investigated the potency of Citrus aurantifolia (Lime fruit), against pathogens, in the different forms in which this fruit plant is used locally (juice of the fruit, burnt rind of the fruit commonly known as “epa-ijebu” in the Yoruba dialect) and the oil obtained from steam distillation of the fruit. The antimicrobial activity of “epa-ijebu” in different solvents was also compared. The solvents include palm-wine (a local alcoholic drink tapped from palm trees), Seaman’s Schnapps 40% alcoholic drink, water, ethanol and fermented water from 3 days soaked milled maize known as “ekan-ogi” or “omidun” in the Yoruba dialect. Antimicrobial activity was carried out by the agar well diffusion. The clinical isolates used included Anaerobic facultative bacteria, namely: Staphylococcus aureus ATCC 25213, Staphylococcus aureus, Salmonella paratyphi, Shigella flexnerii, Streptococcus faecalis, Citrobacter spp, Serratia spp, Klebsiella pneumoniae, Pseudomonas aeruginosa, Escherichia coli ATCC 25922, and Escherichia coli; Fungi such as Aspergilus niger and Candida albicans; and Anaerobes which includes Bacteroides spp, Porphyromonas spp, and Clostridium spp. Crude extracts of all solvents used varied in zones of inhibition. The anaerobes and the Gram-positive bacteria were susceptible to all the extracts with minimum inhibitory concentration (MIC) ranging from 32mg/ml-128g/ml. The activity against the fungi showed only the oil extract potent for A. niger, while Candida albicans was susceptible to all the extracts with MIC ranging from 256mg/ml-512mg/ml. The Gram-negatives have MIC ranging from 64mg/ml-512mg/ml. Minimum bactericidal concentration (MBC) ranged between 32mg/ml to 512mg/ml depending on isolates and extracting solvent. The oil and palm-wine extract of “epa-ijebu” showed greater activity than the other extracts. The killing rate of the schnapps extract on S. aureus and E. coli was 1 and 3.5 hours respectively.